Penerapan Hukuman Dalam Upaya Memperbaiki Ahklak Siswa di Sekolah Smpn 4 Kecamatan Guguak Kabupaten Lima Puluh Kota - Qulbi, Sovia; D, Deswalantri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research is based on the application of punishment in improving students' morals, this is marked by the morals of students who like to come in when the teacher is explaining the lesson and also students who like to talk to friends when the teacher is explaining in front of the class, if this continues to be allowed then students will not understand the importance of having good morals, researchers feel it is very important to conduct research on the application of punishment in an effort to improve students' morals. The type of research used is descriptive qualitative, key informants are teachers and students and supporting informants are the principal. Data collection methods are observation and interview methods. Data analysis techniques used to examine all data, data reduction and data display. This study shows that students who come in and out when the teacher explains the lesson and talk when the teacher explains the lesson in the actions that the teacher will give to students are through notifications, reprimands, warnings and the last action taken by the teacher is to give punishment, and there are also forms of student morals that show the nature of lying, arrogant, betrayal, arrogance and envy with this the teacher will give punishment to students so that they can improve student morals into good morals by giving this punishment the teacher hopes that students will understand the importance of having good morals.